2011
DOI: 10.1262/jrd.10-181a
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Downregulating DNA Methyltransferase 1 Transcript by RNA Interference on DNA Methylation Status of the Satellite I Region and In Vitro Development of Bovine Somatic Cell Nuclear Transfer Embryos

Abstract: Abstract. For the successful production of cloned animals by somatic cell nuclear transfer (NT), the epigenetic status of the differentiated donor cell is reversed to an embryonic totipotent status. However, in NT embryos, this process is aberrant, with genomic hypermethylation consistently observed. Here, we investigated the effects of silencing DNA methyltransferase 1 (DNMT1) mRNA by small interfering RNA (siRNA) on the DNA methylation status of the satellite I region and in vitro development of bovine NT em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 47 publications
5
33
0
Order By: Relevance
“…However, in cloned embryos, continuous expression of Dnmt1s leads to aberrant demethylation (Chung et al, 2003;Yamanaka et al, 2011), and our results also showed that Dnmt1 transcripts were higher in porcine cloned embryos before the 8-cell stage. Additionally, Dnmt1 and Dnmt3a were not effectively activated after ZGA, possibly explaining the cause of incomplete DNA methylation reprogramming and low development of cloned embryos (Huan et al, 2014;Yamanaka et al, 2011). Furthermore, the expression patterns of Dnmt1 and Dnmt3a and the development of cloned embryos in IVF and NA embryos also reveal that effective silence and activation of Dnmts are essential for normal development of early embryos.…”
Section: The Developmental Competence Was Positively Correlated With supporting
confidence: 66%
See 1 more Smart Citation
“…However, in cloned embryos, continuous expression of Dnmt1s leads to aberrant demethylation (Chung et al, 2003;Yamanaka et al, 2011), and our results also showed that Dnmt1 transcripts were higher in porcine cloned embryos before the 8-cell stage. Additionally, Dnmt1 and Dnmt3a were not effectively activated after ZGA, possibly explaining the cause of incomplete DNA methylation reprogramming and low development of cloned embryos (Huan et al, 2014;Yamanaka et al, 2011). Furthermore, the expression patterns of Dnmt1 and Dnmt3a and the development of cloned embryos in IVF and NA embryos also reveal that effective silence and activation of Dnmts are essential for normal development of early embryos.…”
Section: The Developmental Competence Was Positively Correlated With supporting
confidence: 66%
“…Before ZGA, a passive demethylation by a DNA replication dependent mechanism is observed in IVF embryos, probably as Dnmt1 is present in the cytoplasm (Rodriguez-Osorio et al, 2010). However, in cloned embryos, continuous expression of Dnmt1s leads to aberrant demethylation (Chung et al, 2003;Yamanaka et al, 2011), and our results also showed that Dnmt1 transcripts were higher in porcine cloned embryos before the 8-cell stage. Additionally, Dnmt1 and Dnmt3a were not effectively activated after ZGA, possibly explaining the cause of incomplete DNA methylation reprogramming and low development of cloned embryos (Huan et al, 2014;Yamanaka et al, 2011).…”
Section: The Developmental Competence Was Positively Correlated With supporting
confidence: 46%
“…After SCNT, the methylation levels of the Nanog promoter and 5¢-UTR were higher than those in IVF embryos, and the methylation of the first exon was also reprogrammed inefficiently, suggesting that incomplete Nanog methylation reprogramming could be the cause of the poor development of cloned embryos. As for the reason for incomplete Nanog methylation reprogramming, it is possible that there is a mechanism that preserves the methylation pattern of donor cells against reprogramming by oocyte factors (Yamanaka et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, gene-specific methylation reprogramming was incomplete in porcine cloned embryos, which probably leads to poor development of cloned embryos. As for the reason for incomplete methylation reprogramming of Oct4 and Thy1 in cloned embryos, it is possible that there is a potential mechanism which preserves the tissue specific methylation pattern of donor cells against reprogramming by oocyte factors [13, 22, 23]. …”
Section: Discussionmentioning
confidence: 99%